2020
DOI: 10.31940/jasafint.v3i2.2133
|View full text |Cite
|
Sign up to set email alerts
|

Accounting Analysis in Accounts Receivable Management to Minimize the Risk of Uncollectible Receivables at ALS Hotel and Resort

Abstract: ALS Hotel and Resort applies a credit policy in its operations. The high level of credit sales owned by the hotel, which is followed by the high number of delinquent receivables, has the potential to become uncollectible accounts. Therefore, proper management of accounts receivable is required. This research aims to determine the effect of the application of accounts receivable accounting treatment on the effectiveness of accounts receivable management in minimizing the risk of uncollectible receivables at ALS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this research, performance is reflected as the account receivable. Account receivable is one of the financial indicators that will increase along with the distribution of credit receivables to the public [19]. In practice, many companies sell their products by providing credit facilities to upgrade the company size through sales volume [19].…”
Section: Performance (Account Receivable)mentioning
confidence: 99%
See 1 more Smart Citation
“…In this research, performance is reflected as the account receivable. Account receivable is one of the financial indicators that will increase along with the distribution of credit receivables to the public [19]. In practice, many companies sell their products by providing credit facilities to upgrade the company size through sales volume [19].…”
Section: Performance (Account Receivable)mentioning
confidence: 99%
“…Thus, the account receivable will increase if the sales through credit extended to the public are more significant than the credit paid by consumers every month. In addition to credit instalments received by consumers, the account receivable can also decrease by write-off credit because the consumer has overdue for some consecutive instalments [19]. So the company immediately declares it a loss.…”
Section: Performance (Account Receivable)mentioning
confidence: 99%
“…Aziz, (2020) found that the company has employed a system to manage their debtors with adequate internal control, but the company was failed to keep a reserve for probable future bad debt. Suwantari et al, (2020) were found that the accounting approach on debtors adhered to applicable accounting standards. But debtor's management of the company was not yet effective.…”
Section: Review Of Literaturementioning
confidence: 99%